Genetic analysis of the E site during RF2 programmed frameshifting - Sanders, Christina L. (Cold Spring Harbor Laboratory Press, 2007)
The roles of the ribosomal E site are not fully understood. Prior evidence suggests that deacyl-tRNA in the E site can prevent frameshifting. We hypothesized that if the E-site codon must dissociate from its tRNA to allow for frameshifting, then weak codon:anticodon duplexes should allow for greater frameshifting than stronger duplexes. Using the well-characterized Escherichia coli RF2 (prfB) programmed frameshift to study frameshifting, we mutagenized the E-site triplet to all Unn and Cnn codons. Those variants should represent a very wide range of duplex stability. Duplex stability was estimated using two different methods. Frameshifting is inversely correlated with stability, as estimated by either method. These findings indicate that pairing between the deacyl-tRNA and the E-site codon opposes frameshifting. We discuss the implications of these findings on frame maintenance and on the RF2 programmed frameshift mechanism.